Optimization and Construction of Single-side Nuclear Magnetic Resonance Magnet - Ji Yongliang; He Wei; He Xiaolong (Institute of Advanced Engineering and Science, 2013)
Single-sided NMR devices can operate under conditions inaccessible to conventional NMR while featuring portability and the ability to analyze arbitrary-sized objects. In this paper, a semi-elliptic Halbach magnet array was designed and built for single-side Nuclear Magnetic Resonance (NMR). We present an easy-to-implement target field algorithm for single-side NMR magnet design based on Gram-Schmidt Orthogonal method. The creating magnetic field of designed magnet structure could achieve best flatness in the region of interesting for NMR applications. The optimizing result shows that the best magnet structure can generate magnetic fields which flatly distributed in the horizontal direction and the gradient was distributed in the vertical direction with gradient of 2mT/mm. The field strength and gradient were measured by a three dimensions Hall probe and agreed well with the simulations. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3460